(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2017)
In this article, two novels by Zoya Pirzad has been investigated considering Fairclough Critical Discourse Analysis. This article is trying to show how ideology and power of male-characters have influenced on female-characters in these novels. This paper shows that males patriarchal dialogues that are influenced by society, law and ideology put female characters in challenge and pushes aside their dialogues. This paper has investigated the influence of tradition, culture, and ideology on family life and particularly on peoples linguistic interactions from gender point of view. It has been found that the dominant discourse is patriarchal and most of novel females are passive. The research method in this article is analytical and analysis unit is sentences and dialogues of Zoya Pirzads two novels.